Faktor-Faktor yang Mempengaruhi Penyaluran Kredit Investasi pada Bank Persero di Indonesia - Mardianti Rukmana; Sri Ulfa Sentosa; Melti Roza Adry (Universitas Negeri Padang, 2019)
This research purpose are to the analyse the minimum reserves, inflation, third parties fund and interest rates on investment loans in terms of lending of investment loans in State Banks in Indonesia. Methods that being used are Ordinary Least Square (OLS), the estimation results show that minimum reserves has a significant on the lending of investment loans in State Banks in Indonesia, inflation has a not significant on the lending of investment loans in State Banks in Indonesia, third parties fund has a significant on the lending of investment loans in State Banks in Indonesia, and interest rates on investment loans has a significant on the lending of investment loans in State Banks in Indonesia.